2021
DOI: 10.1177/15593258211042161
|View full text |Cite
|
Sign up to set email alerts
|

Poor Uncorrected Visual Acuity and Association With Sleep Duration and Screen Time: A Dose–Response Relationship Study

Abstract: Background We aimed to investigate the prevalence of poor uncorrected visual acuity and the difference among students with different ages and residential areas in the Northeast of China. The relationships between screen time, nighttime sleep duration, and poor uncorrected visual acuity would be explored. Methods It was a cross-sectional study using multi-stage stratified random sampling method to recruit participants. 2149 students have completed questionnaires and underwent visual acuity examinations. The dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…From our analysis, besides sleep duration, there are 72.3% and 76.6% of other factors that affect the visual acuity of the right eye and left eye. The study conducted among 2.419 students ages 14-18 years old in China [28] found that there is a relationship between sleep duration and poor visual acuity. According to the article [28] , the biological processes controlling sleep and ocular development overlap, which may contribute to the visual acuity condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From our analysis, besides sleep duration, there are 72.3% and 76.6% of other factors that affect the visual acuity of the right eye and left eye. The study conducted among 2.419 students ages 14-18 years old in China [28] found that there is a relationship between sleep duration and poor visual acuity. According to the article [28] , the biological processes controlling sleep and ocular development overlap, which may contribute to the visual acuity condition.…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted among 2.419 students ages 14-18 years old in China [28] found that there is a relationship between sleep duration and poor visual acuity. According to the article [28] , the biological processes controlling sleep and ocular development overlap, which may contribute to the visual acuity condition. The circadian rhythm regulates sleep through melatonin, which is controlled by mutual interactions with retinal dopaminergic circuits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the number of myopia patients in China is increasing steadily. In fact, the incidence of myopia in 6-year-old children is 14.5%, but increases to 36.0% in primary school students, 71.6% in junior high school students, and 81.0% in senior high school students 26 , 27 , suggesting that myopia is in a progressive trait, causing serious damage to patients' vision and increasing burden to families and societies. Therefore, how to effectively prevent the onset of myopia and control the progression of myopia has become critical issues in this world.…”
Section: Discussionmentioning
confidence: 99%
“…The logarithm of the minimum angle of resolution (LogMAR) chart by ophthalmologists was used ( 24 ). LogMAR (using the Standard for Logarithmic Visual Acuity Charts, GB/T 11533-2011 of the Standardization Administration of the People's Republic of China) is the “gold standard” used by majority of clinical trials or interventions ( 25 , 26 ). Poor visual acuity was defined as a UCDVA (LogMAR) < 5.0.…”
Section: Methodsmentioning
confidence: 99%